Effects and Interventions of Pressure Injury Prevention Bundles of Care in Critically Ill Patients: A Systematic Review - Trisnaningtyas, Wenny; Retnaningsih, Retnaningsih; Rochana, Nana (Nurse Media Journal of Nursing, 2021)
Background: Many studies on pressure injury prevention bundles have been conducted outside the Intensive Care Unit (ICU). The bundles, which include multi interventions, have proven effective in reducing pressure ulcer incidents compared to a single intervention. However, the existing review studies on pressure injury prevention in ICUs still only investigate a single intervention rather than multi interventions. Only few reviews, to our knowledge, involves prevention bundle strategies in the ICU.Purpose: This study aims to review the effects of the pressure injury prevention bundles of care on the incidents of pressure injury in critically ill patients and the intervention measures of the care bundles.Methods: This review searched published articles from several databases, namely EBSCO, ScienceDirect, PubMed, ProQuest, Google Scholar, and Scopus from 2009 up to 2020. PRISMA flowchart was used to select relevant articles using several inclusion and exclusion criteria, resulting in 17 article from 50 eligible full-text articles for assessment. The included studies were assessed for their quality using Joanna Briggs Institute (JBI) critical appraisal tools. The synthesis was then conducted narratively.Results: As many as 17 studies, which mostly had good quality yet evidence level of II, were included in the analysis. The findings showed that the pressure injury prevention bundles of care decreased pressure injury incidents as many as 4.3%-36.2% in developed countries and 4.16%-21% in developing countries. Moreover, the bundles of care which significantly reduced the incidents of pressure injury consisted of 7 intervention measures, which were pressure injury risk assessment using Cubbin Jackson scale, skin assessment and care, repositioning, nutrition, education, support surface, and medical device care.Conclusion:The review concluded that the pressure injury prevention bundles of care in critically ill patients significantly reduced the incidents of pressure injury. The study recommends more studies with stronger evidence levels to carry out and utilize 7 intervention measures as a preventive standard of care in critically ill patients.Â